Six cases - Shearer, Charles W. (The University of Edinburgh, 1943)
i. Pernicious anaemia; II. Chronic cholecystitis; III. Angina pectoris; IV. Hypertensive encephalopathy; V. Congestive cardiac failure, auricular fibrilization and mitral stenosis; VI. Nephrosis.
Six cases: the Wightman Prize in Clinical Medicine, 1943